Digital skills critical for education: Video analysis of students' technology use in Norwegian secondary English classrooms - Kure, Astrid Elisabeth; Brevik, Lisbeth M.; Blikstad‐Balas, Marte (Journal of computer assisted learning, 2023)
Background Globally, digital skills are a crucial aspect of education that schools should develop systematically. Research on digital skills tends to be measured using self‐reports, performance tests or interventions. There is less knowledge about student and teacher uptake of technology in school, making it important to investigate the actual use of technology and digital skills in authentic classroom settings. Objectives This study contributes unique baseline data concerning students' use of technology and digital skills across mandatory English courses in real classroom settings in secondary schools in Norway over time. Methods The study adapted a national framework for digital skills into an observation protocol. With it, this study analysed videos from 60 naturally occurring English lessons in 13 English classes at seven lower secondary schools over two school years (grades 9 and 10), following 186 students (aged 13–15) and 10 teachers. Results and Conclusions Students used digital skills critical for education in half of the video‐recorded English lessons, with more digital skill use at some schools over time. The main finding across classrooms and school years regards students' use of basic, not advanced, digital skills. Takeaways Although teachers provide opportunities for students to use digital skills in school, more advanced skills are needed. This work calls for continued use of video recordings to provide systematic comparisons of potential shifts in students' digital skills in real English secondary classroom settings over time. Lay Description What is currently known Digital skills is a crucial aspect of education globally Student and teacher uptake of technology varies extensively Most studies on the use of digital technology concern self‐reports and interventions Few studies exist concerning the actual use of digital skills in the classroom What this paper adds Video recordings from seven English classrooms across two school years are analysed. A framework for digital skills is adopted and used as observation protocol Attention is given to the difference between basic and advanced digital skills How technology is actually used matters more than how much technology is available Implications of study findings for practitioners Teachers should offer opportunities for students' use of digital skills in the classroom Subject‐specific use of digital skills should be prioritized There is a need for more emphasis on reflection and digital judgement We need to encourage the use of advanced digital skills and not only basic skills